A VIEWPOINT ON ECONOMY STUDENTS' PERCEPTIONS REGARDING THE PROMOTION PROCESS OF TOURISM PRODUCTS USING ONLINE MARKETING - Silvia, MUHCINA; Andreea-Daniela, MORARU (Strategii Manageriale)
Among the tools that are used in promotional activity in tourism, the online marketing opens the possibility to promptly create offers, meet buyers' demands, and strengthen customer relationships. The online marketers consider that the Internet is a modern technology that allows firms to connect business partners, to identify more rapidly the consumers' needs, to understand and answer on individual demand. The aim of this paper is to emphasize the importance of online marketing in the process of promotion and distribution of tourism products, starting from an empirical research conducted among economic sciences faculty students. The results of this work may provide a partial image of the young people's opinion about online marketing as a tool of marketing communication, and may be approached as a modest guide for tourism marketers in the process of creating, promoting and distributing tourism offers.